2020
DOI: 10.1126/sciimmunol.aay1863
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of PD-1 in myeloid cells induces antitumor immunity

Abstract: PD-1, a T cell checkpoint receptor and target of cancer immunotherapy, is also expressed on myeloid cells. The role of myeloid-specific versus T cell–specific PD-1 ablation on antitumor immunity has remained unclear because most studies have used either PD-1–blocking antibodies or complete PD-1 KO mice. We generated a conditional allele, which allowed myeloid-specific (PD-1f/fLysMcre) or T cell–specific (PD-1f/fCD4cre) targeting of Pdcd1 gene. Compared with T cell–specific PD-1 ablation, myeloid cell–specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
297
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 328 publications
(333 citation statements)
references
References 72 publications
12
297
1
Order By: Relevance
“…Interestingly, PD-1 deficient myeloid progenitors also had increased cholesterol synthesis which is required for the differentiation of inflammatory macrophages. Additionally, PD-1 ablation on myeloid cells decreased tumor growth more effectively than T-cell specific PD-1 ablation in a murine fibrosarcoma and melanoma models ( 109 ). Cumulatively, PD-1/PD-L1 blockade or ablation on myeloid cells promotes phagocytosis in macrophages, reprogramming of myeloid progenitors and even furthers myeloid differentiation via metabolic pathways.…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
“…Interestingly, PD-1 deficient myeloid progenitors also had increased cholesterol synthesis which is required for the differentiation of inflammatory macrophages. Additionally, PD-1 ablation on myeloid cells decreased tumor growth more effectively than T-cell specific PD-1 ablation in a murine fibrosarcoma and melanoma models ( 109 ). Cumulatively, PD-1/PD-L1 blockade or ablation on myeloid cells promotes phagocytosis in macrophages, reprogramming of myeloid progenitors and even furthers myeloid differentiation via metabolic pathways.…”
Section: Methods To Prevent Myeloid Cell Contribution To Cancer Growtmentioning
confidence: 99%
“…Recent studies revealed that the PD-1:PD-L1 axis is activated in CMP and GMP myeloid progenitors that accumulate during cancer-driven emergency myelopoiesis ( 126 ). This is an early event that occurs during the growth of cancer cells and occurs even before the tumor obtains a detectable size.…”
Section: Signaling and Function Of The Pd-1 Pathway In Innate Immunementioning
confidence: 99%
“…Thus, antitumor T cell responses are guided by the consequences of PD-1 signaling in myeloid cells, and PD-1 ablation in T cells, alone, might not be sufficient to promote sustained antitumor function. Instead, it might rather work against antitumor immunity by promoting the accumulation of terminally differentiated T effector cells that promote the generation of MDSCs ( 126 ). Consistent with these findings, triggering PD-1 on monocytes from patients with chronic lymphocytic leukemia hampers glycolysis, phagocytosis, and Bruton’s tyrosine kinase signaling, whereas disrupting PD-1/PD-L1 signaling reverses these immune metabolic dysfunctions ( 124 ).…”
Section: Signaling and Function Of The Pd-1 Pathway In Innate Immunementioning
confidence: 99%
“…Thus, cholesterol production in MDSCs can be inhibited in the presence of PD-1. Therefore, the metabolic reprogramming of emergent myelogenesis and effector myeloid cell differentiation may be the key mechanism of anti-tumor immunity mediated by PD-1 blocking [ 55 ]. In addition, liver X receptors (LXRα and LXRβ) are transcription factors of the nuclear hormone receptor family.…”
Section: Metabolism Of Mdscsmentioning
confidence: 99%
“…In a hypoxic environment, MDSCs inhibit T cell metabolism by hoarding key amino acids [ 55 ]. MDSCs deplete l -cysteine by depletion and sequestration of l -cysteine, resulting in the stagnation of T cell proliferation [ 2 ].…”
Section: Metabolism Of Mdscsmentioning
confidence: 99%